Synthesis and evaluation of an acyl-chain unsaturated analog of the Th2 biasing, immunostimulatory glycolipid, OCH - Velmourougane, Geetha (2009)
An α-galactosyl ceramide (α-GalCer) 2 was synthesized and evaluated for its ability to stimulate iNKT-cell proliferation and elicit T-helper cytokines, IL-4 and IFNγ. Compound 2 combines the acyl chain of the potent, Th2 biasing α-GalCer 1 with a sphingoid base of the same length as that found in OCH, which also exhibits Th2 skewing, Such complementation may enhance cytokine bias, which is thought to be important for therapeutic applications of iNKT cell stimulation. Two related α-GalCers, 3 and 4, with saturated acyl chains were prepared for comparison.